2010
DOI: 10.1002/ejic.200900980
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Ser‐Hydrolase Labelling with a Luminescent Organometallic NCN–Platinum Complex

Abstract: The synthesis, spectroscopic properties and protein-binding studies of a novel luminescent organometallic NCN-platinum complex are described. The luminescent organometallic complex was linked to a serine hydrolase reactive phosphonate group by means of click chemistry, and was ex-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…The desired product was not isolated under any of the conditions employed with unreacted azidoperfluorodecane and a black paramagnetic solid resulting from the decomposition of the complex. It has previously been noted that click reactions involving compounds with metal-chloride bonds are problematic [20].…”
Section: Resultsmentioning
confidence: 99%
“…The desired product was not isolated under any of the conditions employed with unreacted azidoperfluorodecane and a black paramagnetic solid resulting from the decomposition of the complex. It has previously been noted that click reactions involving compounds with metal-chloride bonds are problematic [20].…”
Section: Resultsmentioning
confidence: 99%
“…A platinum(II) complex has been modified with a phosphonate inhibitor to generate a site-specific luminescent labeling reagent [Pt(N^C^N)Cl] (11) for serine hydrolase. 23 Excitation of the complex results in emission at 490 nm in CH 2 Cl 2 . Incubation of cutinase and the complex leads to a loss of ester-hydrolysis activity of the enzyme, which has been ascribed to the occupation of its serine active site by the complex.…”
Section: Wendell Lawmentioning
confidence: 99%
“…These usually incorporate bulkier aromatic or exchange-inert ligands around the Pt coordination sphere to discourage Pt-alkyne interactions. [8] De Sousa et al reported a moderately unhindered propargyl-containing chloroquinoline derivative coordinated to Pt II . [9] By contrast, Parker and co-workers reported on the incompatibility of cis-[Pt(NH 3 ) 2 -(OH 2 ) 2 ] 2+ with a small alkyne-containing O,O'-bidentate ligand in aqueous solution.…”
mentioning
confidence: 99%